Review: Pharmacological role and organic effects (good & adverse) of Statins - Ghasaq Sami Mshary; Cristina Castillo Rodriguez (Genius Journals, 2023)
Statins are a group of compounds with a polyketide structure that are produced by fungal secondary metabolism and have the ability to suppress the activity of HMG-CoA (hydroxyl methyl glutaryl-coenzyme A)enzyme. The impact of statins on histone deacetylase a regulator genetic modifier. Simvastatin, rosuvastatin, atorvastatin, fluvastatin, and pravastatin are the five statins with worldwide authorizations for use. Medications that separate and purify Aspergillus tamari are statin. Due to the existence of methanesulphonamide and their hydroxyl-moiety molecules, some statins are lipophilic while other are hydrophilic. Numerous studies have demonstrated the usefulness of statins as an anticancer, antifungal, antioxidant, and cholesterol-lowering drug. Statins are known to reduce platelet activation by various mechanisms. Numerous studies have demonstrated that this class of statins we used either alone or in combination with other drugs as an anticancer drug. If statins are used with cytochrome P450 inhibitors or other statin metabolism inhibitors that increase blood levels, myopathy and Rhabdomyolysis are the most serious adverse effect of statin intake, but they occur rarely. This article reviews and discusses available information on Simvastatin and atorvastatin as a statin
Keywords: Statins; Effects; Adverse effect; Cholesterol